The relationship between auditory processing disorder and articulation disorders - Safa Alqudah; Lama Al-rashed; Lelas Mansi (PLoS ONE, 2025)
Purpose Auditory processing disorder (APD) may attribute to certain speech problems, as auditory processing plays a vital role in phonetic development during childhood. This research investigates the incidence of APD in individuals with misarticulations of the /r/, /s/, /k/, /θ/, /dʒ/, and /q/ speech sounds. These sounds represent different places of articulation, manners of articulation, and phonation. Method A total of 51 participants with articulation disorders aged 6–18 years underwent conventional peripheral assessments, including otoscopic examination, immittance measurement, and audiometry. Central auditory processing was also evaluated using a battery developed by Frank Musiek. Results Central auditory processing evaluations revealed abnormalities in 37 of 51 participants (72.55%). Correlations between various sound misarticulations and APD were identified: 69.5% for /r/, 40% for /s/, 80% for /k/, 100% for /θ/ and /q/, and 83.3% for /ʤ/. Conclusion The correlation between articulation disorders and APD varies depending on the specific sound affected. Further research is needed to establish clearer associations between different articulation disorders and APD. These findings underscore the importance of assessing central auditory system function in patients with articulation disorders before initiating speech therapy.